Cover Feature: New Water‐Soluble Cluster Compound {Zn(en)3}3[V15Sb6O42(H2O)]⋅ (Ethylenediamine)3⋅10 H2O as a Synthon for the Generation of Two New Antimonato Polyoxovanadates (Chem. Eur. J. 21/2018). Issue 21 (19th February 2018) - Mahnke, Lisa K.; Warzok, Ulrike; Lin, Mengxi; Näther, Christian; Schalley, Christoph A.; Bensch, Wolfgang
Abstract : A new compound featuring the V15 Sb6 O42 core exhibits a remarkable solubility and stability in water. Electrospray ionization mass spectrometry (ESI‐MS) provides evidence of the slow transformation into a more vanadium‐poor and more antimony‐rich compound. Applying the new V15 Sb6 O42 compound as a synthon, two additional and new antimonato‐polyoxovanadate compounds containing the V15 Sb6 O42 cluster could be synthesized within a short reaction time of 24 h. More information can be found in the Full Paper by W. Bensch et al. onpage 5522 .